PERKEMBANGAN RISET OPERASI DAN MODELNYA - Lokot Muda Harahap; Ahmad Hafiz Nasution; Yulia Rahma; Ryan Alfandi; Putri Elma; Rizky Mardewina; Jesavael Nico Voellers Silaban (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to understand and identify the development of operations research and its model as a problem solving technique. Operations research can be seen as a combination of art and science. The science lies in the use of mathematical techniques and algorithms to solve problems, while as an art, the success of this mathematical model solution is very dependent on the creativity and ability of the decision maker in solving the problem. Data were collected from articles and national journals published in the last 5 years, with related keywords such as "development of operations research", "operations research", and "operations research models". Analysis was carried out on 10 articles that met the inclusion criteria. The research results show that the development of operations research has had a major influence on management organizations. Both the number and variety of applications are growing very rapidly. The development of operations research represents fundamental progress achieved at an early stage in the development of existing techniques for operations research. This research aims to serve as a guide for everyone who wants to learn and deepen their knowledge. Apart from that, the aim is also to provide enlightenment to educators, students, educational practitioners, managers of educational institutions, and the general public, in order to create a golden generation with broad knowledge and insight. By implementing these recommendations, it is hoped that the development of operations research can be well understood so that it can help students build professionalism and broad understanding in the field of operational research.